Escola e cidadania nas diretrizes das políticas educacionais para a educação básica - Barbosa, Rosa Amélia (2016)
This work is part of the research process undertaken by the Postgraduate Studies in Education Program (PPGED) at the Federal University of Uberlandia (UFU) related to the State, Policy and Management Education research line (EPGE). It inquiries about the understanding of the official documents and how they present the relationship between citizenship and education, developing a theoretical reflection up the concept of citizenship and, also, a survey of the inchoate (or not) about this concept in the Brazilian legal provisions, starting by the 1988 Federal Constitution, the National Education Bases and Guidelines Law No. 9394/96, the National Basic Education Curriculum Guidelines and specifically the National Secondary Education Curriculum Guidelines. The emphasis in Secondary Education is due to the condition of this is the last stage from the basic education, being a defining moment for the compliance of the legal provisions about quality education expressed in the guidelines as a nation project concepts. In this sense, it is analyzed the possibilities and challenges of public policies about education in relation to the construction of citizenship at school and its relationship to the state, society, democracy and participation. To this end, a basic education school was inserted in the context of analysis, and documents, such as the Political Pedagogical Project and the teacher s secondary education course plans have been used as a source of collecting data as an attempt to identify, in the documents of the school, the relationship between citizenship and educational processes. The metodology adopted to implement the research was the document analysis, starting with the official documents in order to link this research to the study of the institution\'s own documents. The research has been organized from the national policy taken from the 1990s, considering the issue of democracy and the implementation of national curriculum guidelines. Finally, we present considerations about the official documents analysis, particularly the National Secondary Education Curriculum Guidelines, raising relevant issues presented in the pedagogical proposal of the school and the teachers\' course plans, and being possible to verify the principles and purposes of the documents forms built up in the school pedagogical practice.